Why have R&D-intensive industries in Japan experienced a recent decline in performance? Evidence from panel data of listed firms in Japanese R&D-intensive industries - Sakai, Hirotsugu (Journal of Business Economics and Management, 2016)
Previous studies show that the rate of return on research and development (R&D) capital is high. However, R&D-intensive industries in Japan have recently experienced a decline in performance. This study estimates the rate of return on R&D capital and physical capital as well as total factor productivity (TFP) to solve this puzzle. The rate of return is properly estimated applying the methods, which deal with simultaneity bias issues. After Japan entered the “lost decade”, the rate of return on R&D capital dropped significantly, while the rate on physical capital did not. This trend cannot be found by the methods without considering the issues, typically used in previous studies. The slowdown of TFP growth occurs coincidentally with a declining rate of return on R&D capital, which suggests the importance of innovations that enable effective use of R&D capital. Considering the trends, the declining rate of return on R&D capital along with the slowdown of TFP growth are the main causes of the low performance of recent R&D-intensive industries. The results of this paper also offer suggestions on economic policies and growth strategies.